PERAN PEREMPUAN DALAM SEJARAH PENDIDIKAN ISLAM: TINJAUAN HISTORIS DAN KONTEKSTUAL - Zulkifli; Lizi Virma Surianti, Elpita Sari, Yudafriyenti, Mursal, Rusydi, Riki Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the historical and contextual roles of women in Islamic education, highlighting their contributions, challenges, and representation across different periods. Despite their significant involvement as scholars, educators, and founders of educational institutions, women’s roles have often been marginalized in mainstream narratives of Islamic educational history. Using a library research method, this study analyzes primary sources such as classical Islamic texts and secondary sources including academic journals. The findings reveal that women have played vital roles in the transmission of religious knowledge and the establishment of learning centers, yet their presence has frequently been overshadowed by patriarchal structures and gender stereotypes. Through feminist discourse analysis inspired by Judith Butler’s theory, this research demonstrates that these gender-based limitations are socially constructed and can be redefined through inclusive educational reforms. The study concludes with the necessity of reconstructing Islamic educational historiography to incorporate gender-sensitive perspectives and to support more equitable policies in contemporary Islamic educational institutions.